THE INFLUENCE OF MACROECONOMIC VARIABLES ON THE INDONESIAN SHARIA STOCK INDEX PERIOD 2018 – 2022 - Widyanti, Lusi; Hidayati, Amalia Nuril (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Raden Fatah Palembang, Indonesia, 2023)
Abstract This study aims to examine the effect of inflation, exchange rates, the BI-7 day reverse repo rate, and world oil prices on ISSI. The research method used is a quantitative method. The samples used in this study were 12 companies registered with ISSI. The data analysis technique in this study used panel data regression with the stages of the Chow test and the Hausman test. As well as testing the hypothesis with the stages of the f test, t test, and the coefficient of determination (R2). The results of this study prove that inflation has a significant negative effect on ISSI. The exchange rate has no significant effect on ISSI. BI-7day reverse repo rate has a significant negative effect on ISSI. And world oil prices have a significant positive effect on ISSI. The conclusion is that simultaneously inflation, exchange rates, BI-7 day reverse repo rate, and world oil prices influence the ISSI for the 2018 - 2022 period. Keywords: BI-7 day reverse repo rate, World oil prices, Indonesian sharia stock index, Inflation, Exchange rate